Health Care SMEs Products Marketing Strategy: How the Role of Digital Marketing Technology through Social Media? - Khaerul Fahmi; Manorang Sihotang; Rastanto Hadinegoro Hadinegoro; Eva Sulastri; Yoyok Cahyono; Suswanto Ismadi Megah (UJoST- Universal Journal of Science and Technology, 2022)
This study aims to describe the use of digital marketing for hospital marketing. This study categorized a literature review, by conducting a critical literature review and containing scientific information, ideas, or findings contained in the body of literature, academically-oriented literature, and formulating theoretical and methodological contributions to certain topics. Then, the data or knowledge obtained will be described in the next part of the writing series systematically (discussion, opinion, methodology, and conclusion) with the following flow easy to understand and understand for readers. Based on the literature review result, this study can be concluded into six points, there are: First, the usage of digital marketing can be applied to hospital marketing service products. Second, the increasing number of patients can be seen based on the positive reviews of patients' assessment data through selected platforms. Third, digital marketing can strengthen the brand image of health facilities, at the same time, it also makes patients to find the hospital location easier. Fourth, digital marketing can be done with various options, either through applications that are designed by the hospital personally or with other variations of digital platforms such as search engine marketing. Fifth, sending marketing by email or social media, added with search engine optimization means offer many opportunities for hospitals to connect with patients, another that is a requirement and important part for healthcare organizations to keep up with marketing trends and up-to-date promotions in order to create a global brand image for future. Sixth, with constant monitoring, supervision, and a commitment to improving quality, hospitals can use digital marketing for promotion effectively